Scheduling of real-time traffic in IEEE 802.11 networks - Afonso, José A. (2004)
Real-time applications require the provision of time-bounded services from the network, however, the scheduling algorithms used in wired networks are not suitable for wireless networks because they assume that the channel is error free. Besides, the scheduler has only a limited knowledge of the arrival processes of the uplink traffic. In this paper, we propose scheduling algorithms for the transport of real-time traffic in IEEE 802.11 wireless LANs which deal with channel errors. We also present the simulation results obtained with these algorithms.